PENGARUH PEMBERIAN REBUSAN DAUN SALAM (Syzygium polyanthum) TERHADAP KADAR ASAM URAT PADA LANSIA - Febriyanti, Mira Andika (Menara Ilmu, 2018)
The purpose of this research is to see the effect of bay leaf decoction on uric acid level inelderly in Kuranji Padang Village in 2016/2017 with Pre-experiment method with onegroup pretest-posttest design approach in the test with T-test. The result of this researchfound the influence of decoction of bay leaves to uric acid level in elderly with p value0.000 (p <0,05). On this occasion, the researchers expressed their gratitude to the Head ofKuranji Urban Village and Puskesmas Belimbing Padang, Stikes Mercubaktijaya Padangthat has facilitated in research and especially Directorate of Research and Service toHigher Education Society (DIKTI) which has helped both in the form of morale andsupport as well as students who have assisted in this research processKey words: decoction, leaf salam, decrease, uric acid, elderly